Nitrogen-doped Li4Ti5O12/carbon hybrids derived from inorganic polymer for fast lithium storage. (1st September 2017) - Zhou, Kuan; Fan, Xiaojing; Chen, Wei; Chen, Fang; Wei, Xiangfeng; Li, An; Liu, Jiehua
Graphical abstract: Highlights: Nitrogen-doped Li4 Ti5 O12 /carbon hybrids were synthesized using inorganic polymer for the first time. Ti, O, C and N elements could be provided by amorphous titanate-crosslinking g-C3 N4 inorganic polymer. N-doped carbon and N-doped Li4 Ti5 O12 contribute synergistically to an improved conductivity of electrode. Nitrogen-doped Li4 Ti5 O12 /carbon hybrids exhibit superior high-rate and cycling performance. Abstract: Spinel Li4 Ti5 O12 (LTO) is the safest commercial anode for power batteries owing to its stability, zero strain and Li dendrites free, but its inherent insulating characteristic seriously limits its high-rate capability. Nitrogen-doped LTO/C (NCLTO) is firstly synthesized by thermal decomposition of an amorphous titanate crosslinking g-C3 N4 inorganic polymer and then reaction with lithium salts utilizing a simple solid state reaction. The doping nitrogen has a fair distribution which allows fast transportation of lithium ions, and the content of nitrogen is tunable through control the decomposition time of g-C3 N4 . It exhibits a better high-rate capability and cycling performance than that of LTO, which delivers a high capacity of 122 mAh g −1 after 500 cycles at a current density of 10C with 102% capacity retention while the capacity retention of only 50.5% for pure LTO. Furthermore, the NCLTO also exhibits an overwhelming advantage of high-rate performance than LTO owing to the introduced conductive nitrogen-doped carbon and TiN.